TOWARDS ALL-UNDER-HEAVEN: CHINA’S GEOECONOMIC STRATEGY IN THE ASIA-PACIFIC REGION - Azzani, Alfariza Dika (UI Scholars Hub, 2025)
This research aims to understand China’s geoeconomic strategy in reshaping the alternative international order in the Asia-Pacific region. China’s economic rise increased its geopolitical influence and significance as a global great power. The Chinese Communist Party (CCP) government, under Xi Jinping, has adopted classical ideas in its foreign policymaking, including tianxia. Tianxia is a classical concept of a hierarchical Sinocentric international order. An empirical study was conducted on several cases of China’s economic policy and analysed with the congruence method to determine the correlation between the tianxia concept and China’s economic policy. Tianxia served as a paradigm and justification for the Xi Jinping administration’s foreign policy making. Additionally, China’s economic expansion background is its economic pragmatism and the rise of Chinese nationalism. The China-led Belt and Road Initiative (BRI), the Shanghai Cooperation Organisation (SCO), the Asian Infrastructure Investment Bank (AIIB), and the Global Development Initiative (GDI) are being utilised to reshape and create a Sinocentric alternative international order. This was supported by China’s economic capabilities and geostrategic position in the Asia Pacific region. China combines constructive and coercive approaches towards the Asia Pacific countries to safeguard its national interests.